Practices and Status of Preparedness of Vulnerable Household in Disaster Management in Disaster Prone Hill Areas of Nepal - Bistha, Raghu Bir (Patan Pragya, 2019)
Preparedness is called wisdom to reduce disaster risk and its undesired economic loss. It saves to 4 USD, if 1 USD is allocated on preparedness to disaster risk reduction (DRR). Therefore, DRR is considered an effective measure to improve preparedness. This paper examines practices and status of preparedness of vulnerable household in disaster management in disaster prone hill areas of Nepal based on primary data collected household survey of the study area of Sot Khola Catchment Areas: Gadhi, Lekhagaon and Kunathari by using descriptive statistics under explorative and descriptive research design. Its result is existing indigenous knowledge, skill and practices as preparedness measures. Almost households have preferred to move safe place as key preparedness measure of households because of their indigenous knowledge, skill and practice. Its effectiveness is more than other options. Therefore, Nepal as a disaster-prone country has to focus specifically on preparedness from local government to the central government for saving life and economic loss.